Evaluation of the Reliability of Hamular Notch-Incisive Papilla Plane (HIP) in Establishing Occlusal Plane - Thapa, Dipak (Orthodontic Journal of Nepal, 2014)
Introduction: There are various recommendations, using both soft tissue and hard tissue landmarks, for the determination ofocclusal plane in dentistry. However, their reliability and accuracy has always been questioned. Hamular notch-Incisive papillaPlane (HIP) is one of such landmarks which is stated to be parallel to occlusal plane; however its reliability needs to be evaluated. Objective: To find the relationship between hamular notch-incisive papilla plane and occlusal plane in dentulous subjects. Materials & Method: 48 dentate subjects with normal Class I occlusion participated in the study. Their maxillary impressionswere made and casts were poured. Each cast was then mounted in the surveyor and HIP plane made parallel to the floorby tripoding method. With the cast in this relation, the vertical distance between HIP and various reference points of occlusalplanes were measured using digital Vernier Caliper. Wilcoxon test was used to find the statistical difference (p<0.05). Result: During evaluation of data, none of the cast showed absolute parallelism between occlusal plane and HIP plane. Themean vertical distance between HIP and incisal edge (INC) was 6.44 mm, whereas between HIP-6RMP and HIP-6LMP were6.41 mm and 6.12 mm respectively. About 81% cases showed parallelism within the range of 2 mm. 2-related sample statistic testshowed no statistically difference (p<0.05) between HIP-INC and HIP-6RMP; and HIP-INC and HIP-6LMP. Conclusion: HIP plane tends to be parallel to occlusal plane and can be used as a clinical guideline in the determination ofinclination of the occlusal plane. DOI: http://dx.doi.org/10.3126/ojn.v4i1.11311 Orthodontic Journal of Nepal Vol.4(1) 2014; 45-47